2019
DOI: 10.1016/j.brainres.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Taking off the training wheels: Measuring auditory P3 during outdoor cycling using an active wet EEG system

Abstract: Mobile EEG allows the investigation of brain activity in increasingly complex environments. In this study, EEG equipment was adapted for use and transportation in a backpack while cycling. Participants performed an auditory oddball task while cycling outside and sitting in an isolated chamber inside the lab. Cycling increased EEG noise and marginally diminished alpha amplitude. However, this increased noise did not influence the ability to measure reliable event related potentials (ERP). The P3 was similar in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
102
4

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(116 citation statements)
references
References 54 publications
10
102
4
Order By: Relevance
“…In this study, we compared ERPs during an oddball task in four conditions: with background traffic sounds (outdoor sounds), background white noise (white noise), silent background with quiet tones (silent‐low), and silent background (silent). We were able to replicate the main findings of a previous study (Scanlon, Townsend, et al, ) in which an increased N1 and decreased P2 amplitude were observed while participants cycled outside. In particular, when we played a recording of outdoor sounds in the background while participants performed a headphone auditory oddball task, the N1 was increased and the P2 was decreased compared to the silent condition.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…In this study, we compared ERPs during an oddball task in four conditions: with background traffic sounds (outdoor sounds), background white noise (white noise), silent background with quiet tones (silent‐low), and silent background (silent). We were able to replicate the main findings of a previous study (Scanlon, Townsend, et al, ) in which an increased N1 and decreased P2 amplitude were observed while participants cycled outside. In particular, when we played a recording of outdoor sounds in the background while participants performed a headphone auditory oddball task, the N1 was increased and the P2 was decreased compared to the silent condition.…”
Section: Discussionsupporting
confidence: 84%
“…However, the modulations in the N1 and P2 were not observed when participants cycled on a stationary bike inside the lab (Scanlon, Sieben, et al, ). Additionally, Scanlon, Townsend, et al () found that alpha power was decreased while participants cycled outside, and previous work by Brandt, Jansen, and Carbonari () has shown that alpha power may be positively correlated with visual N1 and P2 amplitudes. However, most literature concerning the auditory N1 and P2 components point to these components being primarily affected by extraneous auditory factors, especially for a task in the auditory modality (Näätänen & Picton, ).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…This marginal effect warrants future study, and the effect of habituation could be teased apart by counterbalancing biking and rest conditions. For example, another study currently in preparation has participants performing the same oddball task while both sitting inside and cycling outside, with an equal number of participants starting in each condition to account for habituation effects (Scanlon, Townsend, Cormier, Kuziek, & Mathewson, ).…”
Section: Discussionmentioning
confidence: 99%